Bias-free driven ion assisted photoelectrochemical system for sustainable wastewater treatment - Dang, Qi (2024)
Photoelectrochemical (PEC) systems have emerged as a prominent renewable energy-based technology for wastewater treatment, offering sustainable advantages such as eliminating dependence on fossil fuels or grid electricity compared to traditional electrochemical treatment methods. However, previous PEC systems often overlook the potential of ions present in wastewater as an alternative to externally applied bias voltage for enhancing carrier separation efficiency. Here we report a bias-free driven ion assisted photoelectrochemical (IAPEC) system by integration of an electron-ion acceptor cathode, which leverages its fast ion-electron coupling capability to significantly enhance the separation of electrons and holes at the photoanode. We demonstrate that Prussian blue analogues (PBAs) can serve as robust and reversible electron-ion acceptors that provide reaction sites for photoelectron coupling cations, thus driving the hole oxidation to produce strong oxidant free radicals at photoanode. Our IAPEC system exhibits superior degradation performance in wastewater containing chloride medium. This indicates that, in addition to the cations (e.g., Na+) accelerating the electron transfer rate, the presence of Cl- ions further enhance efficient and sustainable wastewater treatment. This work highlights the potential of utilizing abundant sodium chloride in seawater as a cost-effective additive for wastewater treatment, offering crucial insights into the use of local materials for effective, low-carbon, and sustainable treatment processes.